Majalah Panjebar Semangat Sebagai Pelestari Bahasa dan Sastra Jawa, Tahun 1998-2013 - Khotimah, Muzamil Chusnul; Maziyah, Siti (Sabda: Jurnal Kajian Kebudayaan, 2021)
This research discusses the background to the founding of Panjebar Semangat magazine as a medium for developing Javanese language and literature, its role as a medium for preserving Javanese language and literature, as well as the efforts made to preserve Javanese language and literature. To examine this problem, this research uses a historical method consisting of four sequential stages, namely heuristics, source criticism, interpretation, and historiography. The research results show that the Panjebar Semangat magazine was founded in 1933. As the name suggests, the aim of establishing the Panjebar Semangat magazine was to spread and ignite the spirit of nationalism to win the independence of the Republic of Indonesia from the hands of Dutch colonial rule. This magazine is a medium for preserving the Javanese language and literature, which has been demonstrated since its inception. This magazine has consistently used Javanese as its language of instruction and has been productive in publishing Javanese language works in literary sections such as Crita Cekak, Taman Geguritan, Crita Sambung, Crita Rakyat, Crita Gambar, and Alaming Lelembut. The efforts made by Panjebar Semangat to develop Javanese literature include giving Literary Prizes to Javanese literature authors whose work is considered good and interesting, creating new rubrics, holding contests or writing competitions for Javanese literature, and developing online media.